Atonement, Returning, and Repentance in Islam - Khalil, Atif (Religions, 2023)
The aim of this article is to demonstrate how in Islam the principle mechanism for atonement lies in tawba (returning, repentance). Divided into four sections, and drawing primarily on the literature of classical Sufism, the analysis begins by defining some key terms related to the idea of atonement, with special attention to the language of the Quran. Then it outlines three conditions of returning, repentance, and atonement, delineated by classical Muslim authorities, before turning to a brief overview of the concept of amending wrongs or settings matters aright. It concludes with some final remarks about the possibilities of atonement available until death, and the soteriological role divine mercy is believed to play in the posthumous states of the soul.